2001
DOI: 10.1111/j.1752-1688.2001.tb03657.x
|View full text |Cite
|
Sign up to set email alerts
|

NEAR‐STREAM LANDUSE EFFECTS ON STREAMWATER NUTRIENT DISTRIBUTION IN AN URBANIZING WATERSHED1

Abstract: We investigated spatial and temporal relationships among surface and subsurface watershed attributes and stream nutrient concentrations in urbanizing Johnson Creek watershed in northern Oregon. We sampled stream water at eight urban and five nonurban locations from March 1998 through December 1999. We sampled eight wells distributed over the two primary aquifers in the watershed. Using a Geographic Information System (GIS), percentages of landuse attributes within a radius of 30, 91, and 152 m from each sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 19 publications
(17 reference statements)
1
36
1
Order By: Relevance
“…The study area was a small urban watershed (32 ha) drained by a tributary to Johnson Creek, in southeast Portland, Oregon ( (Sonoda et al 2001). The study site lies on the Troutdale Gravel aquifer that dates back to the Pleistocene, ranges from 20 to 120 m thick, and generally is composed of a consolidated sandy gravel layer (Sonoda et al 2001).…”
Section: Study Areamentioning
confidence: 99%
“…The study area was a small urban watershed (32 ha) drained by a tributary to Johnson Creek, in southeast Portland, Oregon ( (Sonoda et al 2001). The study site lies on the Troutdale Gravel aquifer that dates back to the Pleistocene, ranges from 20 to 120 m thick, and generally is composed of a consolidated sandy gravel layer (Sonoda et al 2001).…”
Section: Study Areamentioning
confidence: 99%
“…The program ArcViewÒ (ESRI, 1997) was used for displaying and analyzing spatial coverage of maps and their corresponding databases created by Metro (1999). Sonoda et al (2001) used GIS analyses to characterize near-stream land use and the relationship with water chemistry in Johnson Creek. They found that nutrients correlated well with near-stream land use characterized within a 30, 91, and 152 m radius around each site.…”
Section: Near-stream Land Use Characterizationmentioning
confidence: 99%
“…In some studies, urban areas had lower stream NO 3 -N concentrations than in agricultural areas (Coulter et al 2004;Sonoda et al 2001) or were between the extremes of intensive agriculture and intact reference sites (Shields et al 2008). Our study shows urban areas had the highest TN concentrations.…”
Section: Meanmentioning
confidence: 48%
“…One explanation for the variability among studies is the obvious differences in type and intensity of agricultural land use and urban development. Baltimore, Maryland (Shields et al 2008), Lexington, Kentucky (Coulter et al 2004), and Portland, Oregon (Sonoda et al 2001) are larger, more heavily urbanized cities than Des Moines, and the agricultural land uses in those studies were more intensive than the cattle grazing in our study. Other factors, such as background levels of nutrients, may be more strongly influenced by natural factors in undeveloped watersheds (e.g., decomposition rates, local N deposition rates) rather than anthropogenic inputs (Clark et al 2000), leading to variability among different study regions.…”
Section: Meanmentioning
confidence: 56%
See 1 more Smart Citation